Academic Freedom and its impact on Organizational Affiliation: An applied study on faculty members at the College of Fine Arts - University of Babylon - Al-salami, Yamama Mudhher Azawi (Journal of Economic, Administrative and Legal Sciences, 2021)
Academic freedom is an important and irreplaceable necessity by the faculty member and it is his right to practice his various activities and express his views, ideas and philosophy without any external pressure exerted on him, and the current research aimed to measure academic freedom in its fields (participation in decision-making, scientific research, teaching Community Service) and its impact on the organizational affiliation of faculty members at the University of Babylon / College of Fine Arts in the Republic of Iraq, the study tool was a survey list consisting of (32) questions, the group was (98), the results reached to That the level of both academic freedom and organizational affiliation was (average), And that there is a statistically significant relationship between academic freedom and organizational affiliation at a level of significance (0.05), and one of the most important recommendations is the need to pay attention to academic freedom by the university presidency and provide financial support to faculty members to conduct their scientific research.